Study on mechanism of action of total flavonoids from Cortex Juglandis Mandshuricae against alcoholic liver disease based on “gut-liver axis” - Liu, Huiru; Meng, Wenwen; Zhao, Dongsheng; Ma, Zhihui; Zhang, Wenguang; Chen, Zhi; Li, Zhengguo; Zhao, Pan (Frontiers in Pharmacology, 2023)
The objective of this study was to investigate the effects and molecular mechanisms of total flavonoids from Cortex Juglandis Mandshuricae (TFC) on preventing alcohol-induced chronic liver injury and regulating gut microbiota in mice. The results showed that oral administration of TFC significantly attenuated alcoholic liver injury in mice. TFC improved lipid accumulation in mice with chronic alcoholic liver injury through activation of the AMPK/PPARα pathway. In addition, TFC maintained the integrity of the intestinal barrier in alcoholic mice, reducing endotoxin leakage from the intestine and further inhibiting the TLR4/NF-B inflammatory pathway. More importantly, TFC regulated the intestinal microbiota composition and certain bacteria, including Akkermansia muciniphila, Lactobacillus and others. At the same time, reduced levels of short-chain fatty acids due to alcohol consumption were restored. In summary, TFC upregulated AMPK/PPARα signaling pathway to improve hepatic fat accumulation and oxidative stress; TFC positively regulated intestinal flora composition to reduce intestinal disorders caused by alcohol consumption, and further inhibited alcohol-induced inflammatory responses through the intestinal-liver axis. The above findings may be the mechanism of TFC's pharmacological effects against alcoholic liver injury.